I CAN BUY MYSELF FLOWERSâ€: A Gender Performativity Analysis of Women’s Empowerment in Miley Cyrus’s Flowers - Stefi Nania Tampubolon; Nur Halfa Nabila; Syarifah Sarah Nurjihan; Nurlaili Fitria; T. Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study analyzes the representation of women’s empowerment in Miley Cyrus’s song "Flowers" (2023) and its contribution to the discourse of self-love and female independence from a feminist perspective. Employing an exploratory-interpretive qualitative research design, the study uses Judith Butler’s theory of gender performativity as the analytical framework. The primary data consist of the complete song lyrics, which were analyzed using the interactive model of Miles et al. (2014) and Creswell’s (2014) qualitative analysis procedures. The findings reveal that women’s empowerment is represented through repeated self-directed actions expressed in the phrase "I can," which emphasizes agency, emotional self-reliance, and personal autonomy. The lyrics further portray selflove through acts of self-care, self-acceptance, and forgiveness, while also representing female independence through the speaker’s ability to define herself beyond romantic relationships. From Butler’s perspective, these repeated actions function as performative acts through which the female persona continuously reconstructs her identity. Furthermore, the song contributes to contemporary discussions of self-love and women’s empowerment by promoting emotional resilience and independence following a romantic breakup. The values represented in the song also support the broader objectives of Sustainable Development Goal 5 (Gender Equality) by encouraging women’s autonomy, self-determination, and empowerment. This study contributes to feminist literary studies by demonstrating how popular song lyrics can function as cultural texts that foster gender awareness and empowerment in contemporary society. Keywords: feminism, women’s empowerment, song lyrics, self-love, gender performativity,popular music